Dyslexia Profiles Across Orthographies Differing in Transparency: An Evaluation of Theoretical Predictions Contrasting English and Greek. (2nd January 2018) - Diamanti, Vassiliki; Goulandris, Nata; Campbell, Ruth; Protopapas, Athanassios
ABSTRACT: We examined the manifestation of dyslexia in a cross-linguistic study contrasting English and Greek children with dyslexia compared to chronological age and reading-level control groups on reading accuracy and fluency, phonological awareness, short-term memory, rapid naming, orthographic choice, and spelling. Materials were carefully matched across languages in item properties and structure. English children with dyslexia were more impaired on reading accuracy and phoneme deletion but not on reading fluency, memory, naming, or orthographic choice. No differences in impairment were observed between words and pseudowords across languages. Orthographic tests targeted specific morphemes to examine the accessibility of functionally distinct word parts across languages. There were no differences in prefix and stem orthographic choice, but English children were less successful in spelling inflectional suffixes despite greater morphological richness in Greek, highlighting the need for additional considerations beyond grain size in cross-linguistic work.